Amperometric biosensor based on zirconium oxide/polyethylene glycol/tyrosinase composite film for the detection of phenolic compounds - Ahmad, Nor Monica; Abdullah, Jaafar; Yusof, Nor Azah; Ab Rashid, Ahmad Hazri; Abd Rahman, Samsulida; Hasan, Md. Rakibul (MDPI, 2016)
A phenolic biosensor based on a zirconium oxide/polyethylene glycol/tyrosinase composite film for the detection of phenolic compounds has been explored. The formation of the composite film was expected via electrostatic interaction between hexacetyltrimethylammonium bromide (CTAB), polyethylene glycol (PEG), and zirconium oxide nanoparticles casted on screen printed carbon electrode (SPCE). Herein, the electrode was treated by casting hexacetyltrimethylammonium bromide on SPCE to promote a positively charged surface. Later, zirconium oxide was mixed with polyethylene glycol and the mixture was dropped cast onto the positively charged SPCE/CTAB. Tyrosinase was further immobilized onto the modified SPCE. Characterization of the prepared nanocomposite film and the modified SPCE surface was investigated by scanning electron microscopy (SEM), Electrochemical Impedance Spectroscopy (EIS), and Cyclic voltamogram (CV). The developed biosensor exhibits rapid response for less than 10 s. Two linear calibration curves towards phenol in the concentrations ranges of 0.075-10 µM and 10-55 µM with the detection limit of 0.034 µM were obtained. The biosensor shows high sensitivity and good storage stability for at least 30 days.